PENGARUH KOMPENSASI, PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP RETENSI KARYAWAN PERUSAHAAN (Studi kasus karyawan PT Bank Rakyat Indonesia Cabang Semarang Pandanaran) - Supriyanto, 15.05.51.0103; Indriyaningrum, Kis (Students' Journal of Economic and Management, 2019)
This study analyzes the effect of Compensation, Career Development and Work Motivation on Employee Retention. The object of this study was employees of PT Bank Rakyat Indonesia Semarang Branch Pandanaran. The sampling technique in this study used a random sampling technique with the Slovin formula. The results of the sample were 152 respondents and the data collection method used a questionnaire (questionnaire) by distributing a list of statements to the respondents in order to obtain information. Data and information collected in this study were processed using version 19 Statistical Package for Social Sciences (SPSS) software, then analyzed using correlation coefficients to test KMO validity, cronbach alpha to test instrument reliability, and multiple linear regression analysis to test the magnitude of influence each independent variable on the dependent variable. The results showed that Compensation had a positive and significant effect on employee retention, Career Development had a positive and significant effect on Employee Retention, Motivation had a positive and significant effect on Employee Retention.